2017
DOI: 10.1038/srep43268
|View full text |Cite
|
Sign up to set email alerts
|

Transcript profiling of two potato cultivars during glycoalkaloid-inducing treatments shows differential expression of genes in sterol and glycoalkaloid metabolism

Abstract: Steroidal glycoalkaloids (SGA) are sterol-derived neurotoxic defence substances present in several members of the Solanaceae. In the potato (Solanum tuberosum), high SGA levels may render tubers harmful for consumption. Tuber SGA levels depend on genetic factors, and can increase as a response to certain stresses and environmental conditions. To identify genes underlying the cultivar variation in tuber SGA levels, we investigated two potato cultivars differing in their SGA accumulation during wounding or light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 59 publications
4
43
0
Order By: Relevance
“…Studies have found that the SGA content of potato tubers varies with time (Percival, ; Dao & Friedman, ). The SGA content in the tubers exposed to light for 96 h was clearly higher than that of control tubers kept in the dark (Nahar et al ., ). However, these studies did not monitor the SGA content in tuber skin or flesh after treatment.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies have found that the SGA content of potato tubers varies with time (Percival, ; Dao & Friedman, ). The SGA content in the tubers exposed to light for 96 h was clearly higher than that of control tubers kept in the dark (Nahar et al ., ). However, these studies did not monitor the SGA content in tuber skin or flesh after treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is very important to reduce the extent of wounding in potato tubers. In addition, it is reported that the activity of the relative enzyme of SGA in potato tubers increased slowly before 11 h and reaches a maximum after 16 h (BergenstrÅhle et al ., ), and the expression of related SGA synthesis genes increased after potato injury (Nahar et al ., ). Therefore, wound could activate the related synthetic genes of SGA in potato, which leads to the increase of SGA content.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations